2020
DOI: 10.1111/bjhp.12480
|View full text |Cite
|
Sign up to set email alerts
|

Stockpiling in the time of COVID‐19

Abstract: Objectives. Consistent with behaviour observed in prior crises, individuals are stockpiling supplies during the novel coronavirus (COVID-19) pandemic. The goal of this study was to describe stockpiling behaviour in response to COVID-19 and investigate individual predictors of stockpiling. Methods. Workers (N = 363, 54.72% male, 44.65% female, 0.63% other; M age = 38.41, SD = 12.48, range = 18-78) were recruited from Amazon's Mechanical Turk and completed a survey about their stockpiling of 13 items, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 18 publications
0
64
1
1
Order By: Relevance
“…We identified eight published studies related to the COVID-19 pandemic with toilet paper hoarding ( Garbe, Rau & Toppe, 2020 ; Kirk & Rifkin, 2020 ; Oosterhoff & Palmer, 2020 ; Sim et al, 2020 ; Miri et al, 2020 ; Micalizzi, Zambrotta & Bernstein, 2020 ; Laato et al, 2020 ; Güzel, 2020 ). One study included a survey of participants focused on toilet paper shopping and stockpiling behaviours ( Garbe, Rau & Toppe, 2020 ), one study conducted a survey of adolescents regarding several pandemic-related behaviours (including hoarding) ( Oosterhoff & Palmer, 2020 ), and another study conducted a survey through Amazon’s Mechanical Turk on stockpiling behaviour (including toilet paper) in response to COVID-19 ( Micalizzi, Zambrotta & Bernstein, 2020 ). One study analysed purchasing behaviour during the COVID-19 pandemic ( Laato et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified eight published studies related to the COVID-19 pandemic with toilet paper hoarding ( Garbe, Rau & Toppe, 2020 ; Kirk & Rifkin, 2020 ; Oosterhoff & Palmer, 2020 ; Sim et al, 2020 ; Miri et al, 2020 ; Micalizzi, Zambrotta & Bernstein, 2020 ; Laato et al, 2020 ; Güzel, 2020 ). One study included a survey of participants focused on toilet paper shopping and stockpiling behaviours ( Garbe, Rau & Toppe, 2020 ), one study conducted a survey of adolescents regarding several pandemic-related behaviours (including hoarding) ( Oosterhoff & Palmer, 2020 ), and another study conducted a survey through Amazon’s Mechanical Turk on stockpiling behaviour (including toilet paper) in response to COVID-19 ( Micalizzi, Zambrotta & Bernstein, 2020 ). One study analysed purchasing behaviour during the COVID-19 pandemic ( Laato et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…One survey of 363 workers in the United States who were recruited from Amazon’s Mechanical Turk inquired about the stockpiling of 13 items, as well as opinions on the COVID-19 pandemic and political affiliation (Democrat vs. Republican) ( Micalizzi, Zambrotta & Bernstein, 2020 ). Of all 13 items, toilet paper was the item most commonly stockpiled (63.2%).…”
Section: Resultsmentioning
confidence: 99%
“…In such contexts, even individuals who had never previously exhibited hoarding behavior may develop an increased attachment to, and urge to accumulate, certain possessions—leading, not to hoarding disorder per se , but to panic buying. In this context, it is worth noting that many of the individual psychological variables identified as being linked to panic buying, such as high neuroticism and low openness and conscientiousness ( 17 ), have been specifically associated with disturbances in attachment both in children and in young adults ( 55 ).…”
Section: Divergent Theoretical Perspectives On Panic Buyingmentioning
confidence: 99%
“…A study from Portugal reported stockpiling in 36% of respondents ( 16 ). In a report from the United States, the most common stockpiled materials were toilet paper (63%), canned foods (59%), staple foods such as rice and bread (53–57%), bottled water (57%), and medications (53%) ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation